Spomini in predmeti v družini - Balážová, Ivana (Etnolog. Nova vrsta (Ljubljana), 2017)
From the viewpoint of the social sciences, everyday objects are not treated merely as something inanimate. According to some theories things are capable of acts and witnessing to historical events and cultural phenomena as well as. Based on the assumption that objects are capable of becoming connected to ideas and consequently influencing people's acts, I carried out a research that provided the basis for this article. The research showed that we can achieve a better understanding of family relationships through certain objects. The research also focused on inheritance, passing on objects within the family, and the preservation of memories in objects.From the viewpoint of the social sciences, everyday objects are not treated merely as something inanimate. According to some theories things are capable of acts and witnessing to historical events and cultural phenomena as well as. Based on the assumption that objects are capable of becoming connected to ideas and consequently influencing people's acts, I carried out a research that provided the basis for this article. The research showed that we can achieve a better understanding of family relationships through certain objects. The research also focused on inheritance, passing on objects within the family, and the preservation of memories in objects.
Keywords: materialna kultura; spominski predmeti; osebni predmeti; družine; Slovaki; Slovakia; terenske raziskave